“Quien no tranza, no avanza”: una aproximación etnográfica al clientelismo político en México - Iñigo González de la Fuente (Centre de Recherches sur les Mondes Américains, 2007)
This is about presenting the first results of the "working camp" that we have doing in two Mexican countries since October 2005. Just in the middle of the campaign of the candidates to the federal Presidency, our main goal is to detect through ethnographic techniques the decisive factors of the political participation and more particularly, the electoral behaviour which is present in the Mexican citizenship. Being this a research to a local level, we aspire to get into the disassion about clientilism with the total security that is given by sharing the daily facts with the political and economical actors from the communities that have been the object of study or research.